Pengaruh Seleksi dan Penempatan Karyawan Terhadap Produktivitas Kerja Pada PT Bank Mandiri (Persero) Tbk Cabang X - Ades Asike (Journal of Research in Business, Economics, and Education, 2021)
This Research aim to know and analyse influence of location of employees to productivity of karyawan pada PT. Bank Mandiri (Persero) Tbk Cabang X, As for used research method [at] this research [of] type qualitative and quantitative by using technique research of analysis of regresi doubled. in determination of sampel counted 34 people, Result of research at a time indicate that selection and location of simultan karyawansecara have an effect on positive and signifikan to Office employees work productivity , Result of research by parsial indicate that selection have an effect on positively and signifikan to Office employees work productivity , and so do for the variable of location of employees indicate that selection have an effect on positively and signifikan to employees work productivity.